Understanding factors influencing the adoption of moxibustion techniques by the population: an extended study based on the UTAUT model - Chengxin Fan; Chengxin Fan; Zina Fan; Qiusha Li; Zixuan Zhao; Zixuan Zhao; Chunxiao Yang; Chunxiao Yang; Zhongming Chen; Zhongming Chen; Wenqiang Yin; Wenqiang Yin (Frontiers in Public Health)
BackgroundTraditional Chinese medicine plays a unique role and has proven efficacy in preventing and treating common and chronic diseases. Moxibustion, as a type of traditional Chinese medicine healthcare therapy, has a broad mass, social, and cultural foundation in China. This study analyzes the pathways and influencing factors of residents' acceptance of moxibustion.MethodsData were collected from 808 residents in 18 cities or districts using whole cluster stratified random sampling. Take the expanded Unified Theory of Acceptance and Use of Technology model scale as the research tool. Data were analyzed by SPSS 25.0 and AMOS 24.0, including descriptive statistics, one-way analysis of variance, structural equation model analysis, and multi-group model analysis.ResultsStructural equation modeling showed that performance expectancy (β = 0.603, p < 0.001), effort expectancy (β = 0.260, p < 0.001), social influence (β = 0.373, p < 0.001), and perceived risk (β = −0.162, p < 0.001) significantly predicted behavioral intention. Facilitating conditions (β = 0.186, p < 0.01) and behavioral intention (β = 0.708, p < 0.001) directly affect usage behavior. The multiple-group analysis found that experiential and chronic disease status played a moderating role in the structural pathways.ConclusionsThe study confirmed that the constructed resident moxibustion technology model can serve as a suitable framework for predicting the factors that influence residents' intention to use moxibustion and their behaviors. Increasing residents' performance expectations and effort expectations, creating a positive social environment, and reducing perceived risk are key factors in enhancing residents' behavior and willingness to use moxibustion.